Latest advances in neoadjuvant therapy for bladder cancer - Rioja, Patricia (2022)
Cisplatin-based neoadjuvant therapy has shown clear benefits in clinical stage II or IIIA muscle invasive bladder cancer (MIBC), achieving an impact in progression-free survival and overall survival. This updated review focuses on neoadjuvant therapy for MIBC, including the current recommendations from international and/or local practice guidelines, as well as studies of new therapeutic agents (immunotherapy, targeted therapy), on top of research on potential biomarkers that may predict response to immunotherapy.